HUBUNGAN ANTARA FAKTOR-FAKTOR INTERNAL DENGAN EVALUASI HASIL BELAJAR MAHASISWA DI AKPER PAMENANG PARE KEDIRI - Cahyono, Aris Dwi (Akademi Keperawatan Pamenang, 2010)
Evaluation result of learning to emphazise to obtainingof information about how acquirement of student inreachingÂ onÂ targetÂ ofÂ specifiedÂ instruction.Â EvaluationÂ resultÂ ofÂ learningÂ canÂ influenceÂ byÂ someÂ factorÂ amongothers motivator factor learn, habit learn and effeciency attend the lecture.TargetÂ ofÂ thisÂ researchÂ isÂ toÂ studyÂ internalÂ factorsÂ relatedÂ toÂ evaluationÂ resultÂ ofÂ learningÂ inÂ AkperPamenang Pare.The research design which used was the cross sectional. The samples taken away from all student mount IItotallyÂ samplingÂ numberÂ ofÂ 48Â student.Â Instrument usedÂ forÂ dataÂ collectingÂ documentationÂ andÂ questtionnaireresultÂ ofÂ evaluationÂ learn evenÂ semesterÂ student (semesterÂ II)Â periodeÂ ofÂ yearÂ 2004/2005.Â DataÂ processingÂ usestatistical test (SPSS) Spearman RhoâS with level of significanceÎ± < 0,05.Result of data processing with SPSS Spearman RhoâS show there are relation between motivation learn withevaluationÂ resultÂ ofÂ learningÂ (Î±Â =Â 0,038),Â thereÂ areÂ relationÂ betweenÂ habitÂ learnÂ withÂ resultÂ ofÂ learningÂ (Î±Â =0,013) and do not there are relation between sufficiency attend the lecture with evaluation result of learning (Î±= 0,455).Conclusion of this research there are relation between motivation factor learn, habit learn and efficiency attendthe lecture with evaluation result of learning student Akper Pamenang Pare. So that motivate to learn, habitlearn and efficiency attend the lecture student require to be improved to beÂ more improve achievement learn, byperforming atuition to studentKeywords: Evaluate result learn, motivation learn,habit learn, efficiency attend the lecture..